2022
DOI: 10.1038/s41467-022-34704-9
|View full text |Cite
|
Sign up to set email alerts
|

Daylight saving time affects European mortality patterns

Abstract: Daylight saving time (DST) consists in a one-hour advancement of legal time in spring offset by a backward transition of the same magnitude in fall. It creates a minimal circadian misalignment that could disrupt sleep and homoeostasis in susceptible individuals and lead to an increased incidence of pathologies and accidents during the weeks immediately following both transitions. How this shift affects mortality dynamics on a large population scale remains, however, unknown. This study examines the impact of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
(93 reference statements)
1
5
0
Order By: Relevance
“…6 14 16 22 37 Moreover, we found that the combined effect of transitions to both spring and autumn daylight saving time was a decrease in the risk of mortality but the decrease was not significant. Similar to a previous study that investigated general mortality risks after daylight saving time in 16 European countries, 28 our finding was also in contrast with the general scientific postulate in the daylight saving time literature that minimal sleep deprivation might lead to an increase in the risk of mortality. 8 20 38 We investigated changes in mortality during a relatively long period, up to eight weeks after the transition to daylight saving time.…”
Section: Comparison With Other Studiessupporting
confidence: 86%
See 1 more Smart Citation
“…6 14 16 22 37 Moreover, we found that the combined effect of transitions to both spring and autumn daylight saving time was a decrease in the risk of mortality but the decrease was not significant. Similar to a previous study that investigated general mortality risks after daylight saving time in 16 European countries, 28 our finding was also in contrast with the general scientific postulate in the daylight saving time literature that minimal sleep deprivation might lead to an increase in the risk of mortality. 8 20 38 We investigated changes in mortality during a relatively long period, up to eight weeks after the transition to daylight saving time.…”
Section: Comparison With Other Studiessupporting
confidence: 86%
“…Evidence from population level studies is lacking, however, particularly on the risks of different causes of mortality associated with transition among the general population. 28 In this study, our aim was to investigate the relation between transition to daylight saving time and the risks of all cause and cause specific mortality among more than 13 million deaths in the US, from 2015 to 2019. We also performed subgroup analyses to identify subpopulations that were vulnerable to shifts in daylight saving time by time zones, age, and race and ethnic group.…”
Section: Introductionmentioning
confidence: 99%
“…Our body clocks track this delaying dawn, thus increasing the mismatch between its phase and our wake time [12]. Although many studies, including those reviewed here, focus on the consequences of the abrupt time change, the range of days to examine before and after the time change has been a topic of debate [1,13 ▪ ,14]. As results from these studies are disseminated, the public's enthusiasm to continue this tradition has waned, with many polls finding a desire to end clock changes [15 ▪ ,16 ▪ ,17].…”
Section: Introductionmentioning
confidence: 99%
“…Transitions into and out of DST have long been associated with adverse outcomes. When all-cause mortality was examined over 14 years in 16 European countries, a significant increase in mortality was noted following the return to standard time, while a significant decrease in mortality was noted with the start of DST [13 ▪ ]. This may have been influenced by an overall upward trend in mortality in the fall and a downward trend in mortality in the spring.…”
Section: Introductionmentioning
confidence: 99%
“…The article “Daylight saving time affects European mortality patterns” by Lévy et al 1 reports associations between all-cause mortality and multiple factors, including the clock time changes between standard time [ST] and daylight saving time [DST] in spring and fall, using data from 1998 and 2012 in 16 European countries. While the abstract reports that mortality decreases for two weeks after the spring change and shows a reverse effect in the fall, Figure 1b/c clearly shows the opposite in the weeks after the transitions: a relative increase from already decreasing mortality trend after the spring change and a relative decrease from the already increasing trend in the fall.…”
mentioning
confidence: 99%